Franklin stays up - Jennings, Sharon; Jeffrey, Sean; Southern, Shelley; Sisic, Jelena (New York : Scholastic, 2003)
Franklin wants to stay up all night, so he invites his friends to an overnight in a his backyard, but they find that staying awake is harder than they thought.
G1
Keywords: Sleepovers -- Fiction; Camping -- Fiction; Turtles -- Fiction; Animals -- Fiction